Expressing time through analogy - Mouheb Aldeen, Deeaa Hussin (Journal of Humanities & Social Sciences, 2019)
The subject of time is of great importance to thinkers, philosophers and linguists, and this study is discusses how to express time through the metaphor, which is an important type of artistic image, which is taught in Arabic rhetoric through the science of statement, and the aim of the study to highlight the ability of analogy to express Tense in multiple ways, the study adopted descriptive analytical method, in describing the phenomenon rhetorical, and then multiplying examples, analysis and discussion. Research began with an introduction, in it; the importance of research, its problem, its objectives, and its components. Then divide the search into three parts by kind of metaphor. Then the conclusion and the results.